2015
DOI: 10.1002/anie.201508626
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Polymer Hydrogel Nanoparticles for Lymph Node‐Targeted Delivery

Abstract: The induction of antigen-specific adaptive immunity exclusively occurs in lymphoid organs. As a consequence, the efficacy by which vaccines reach these tissues strongly affects the efficacy of the vaccine. Here, we report the design of polymer hydrogel nanoparticles that efficiently target multiple immune cell subsets in the draining lymph nodes. Nanoparticles are fabricated by infiltrating mesoporous silica particles (ca. 200 nm) with poly(methacrylic acid) followed by disulfide-based crosslinking and templat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
106
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 136 publications
(108 citation statements)
references
References 25 publications
0
106
0
2
Order By: Relevance
“…Degradable polymer nanogels were prepared by self-assembly of amphiphilic block copolymers composed of a hydrophilic, PEG-like polymer block based on methoxy triethylene glycol methacrylate (mTEGMA) and a hydrophobic polymer block based on pentafluorophenyl methacrylate (PFPMA) (21). The PEG-like hydrophilic block was used to provide nanoparticle stability and tissue mobility, as recently demonstrated by us and others (15,22,23). The PFPMA block allows for self-assembly into nanoparticles in polar aprotic solvents (such as DMSO) followed by 1-(4-(aminomethyl)benzyl)-2-butyl-1H-imidazo [4,5-c]quinolin-4-amine (IMDQ) ligation and cross-linking of the PFP esters with bisamines (24) without facing competing hydrolysis reactions that would occur in aqueous medium (25).…”
mentioning
confidence: 99%
“…Degradable polymer nanogels were prepared by self-assembly of amphiphilic block copolymers composed of a hydrophilic, PEG-like polymer block based on methoxy triethylene glycol methacrylate (mTEGMA) and a hydrophobic polymer block based on pentafluorophenyl methacrylate (PFPMA) (21). The PEG-like hydrophilic block was used to provide nanoparticle stability and tissue mobility, as recently demonstrated by us and others (15,22,23). The PFPMA block allows for self-assembly into nanoparticles in polar aprotic solvents (such as DMSO) followed by 1-(4-(aminomethyl)benzyl)-2-butyl-1H-imidazo [4,5-c]quinolin-4-amine (IMDQ) ligation and cross-linking of the PFP esters with bisamines (24) without facing competing hydrolysis reactions that would occur in aqueous medium (25).…”
mentioning
confidence: 99%
“…They were composed of a hydrophilic, poly(ethyleneglycol) (PEG)-like polymer block based on methoxytriethylene glycol methacrylate (mTEGMA) and a hydrophobic polymer block based on pentafluorophenyl methacrylate (PFPMA) that can be block copolymerized by reversible addition fragmentation chain-transfer (RAFT) polymerization [18][19][20]. The PEG-like hydrophilic block was used to provide nanoparticle stability and tissue mobility as recently demonstrated by us and others [6,9,21]. The PFPMA block allowed for self-assembly into nanoparticles in polar aprotic solvents (such as DMSO) followed by functionalization and crosslinking of the PFP esters with bisamines (containing a degradable linker) [22] without facing competing hydrolysis reactions that would occur in aqueous medium [23].…”
mentioning
confidence: 99%
“…Similarly, Kim et al have reported that both small cationic and anionic poly(γ-glutamic acid)-based nanosystems (30–60 nm) were able to self-drain to the closest lymph node [55]. Finally, the presence of PEG on the surface of the nanocarriers, that usually renders their surface charge close to neutrality, has a positive effect in the drainage to the LN [5659]. This does not necessarily translate into a higher interaction with immune cells [51,56,60], as the degree of pegylation and the PEG molecular weight may have an impact on the NP opsonization [8,61].…”
Section: Access Of Nanostructures To Target Cellsmentioning
confidence: 99%